Easily identifiable congental anomalies: Prevalence and risk factors - "Tootoonchi P " (Acta Medica Iranica, 2003)
To determine easily identifiable congenital anomalies (CA) prevalence and risk factors in the first 24 hours of life in a cross-sectional study we assessed 2291 live born neonates at four teaching hospitals from September 1999 until March 2000 in the south of Tehran. Data were collected by a structured form which contained neonatal characters including sex, gestational age, birth weight, history of CA in siblings, type of CA if there was any and maternal characters including maternal age, history of chronic illness, history of reproduction (including gravidity, parity, infertility and abortion) and conditions during recent pregnancy (including multiple gestation, vaginal bleeding, drug taking, smoking, exposure to X-ray and gestational illness). The prevalence of CA was 2.3% (55 cases). There were 29 males (52.7%) and 26 females (47.3%). Seventeen cases (30.9%) and 15 cases (27.3%) were low birth weight (LBW) and premature, respectively. There was positive history of CA in siblings of only 2 cases (3.6%). Mother of one case (1.8%) had history of drug ingestion during pregnancy. 14.5% (8) and 9.1% (5) of cases, mothers had chronic or gestational illnesses, respectively. Overall musculoskeletal system (30.59%), central nervous system (18.82%) and genital anomalies (16.48%) were accounted as the most common CA. There was statistical significance between CA and birth weight (Odds ratio [OR] 2.51, Confidence Interval [CI] 1.17-5.37).